Transdiagnostic mechanisms in depression and anxiety: The role of rumination and attentional control - Hsu, Kean J. (J Affect Disord, 2015)
BACKGROUND: Deficits in attentional control have been hypothesized to cause rumination, suggesting that the relationships between attentional control and clinical symptoms may be mediated in part by rumination. However, to date, no clinical study has examined these constructs transdiagnostically in a path analysis model. METHODS: Fifty-one adults presenting for treatment completed measures of self-reported attentional control, rumination, and depression and anxiety symptoms. A bias-corrected path analysis-based approach was employed to test whether indirect (i.e., mediating) effects of rumination were significantly associated with the direct effects of attentional control on depression and anxiety symptoms. Separate models for depression and anxiety symptoms were tested along with reverse models using attentional control as a proposed mediator. RESULTS: The relationship between attentional control and clinical symptomatology (i.e., both depression and anxiety symptoms) was mediated by rumination. Poor attentional control was associated with more rumination and consequently more severe symptoms of depression and anxiety. The reverse relationship (i.e., attentional control mediating the relationship between rumination and depression or anxiety symptoms) was not significant. LIMITATIONS: Study design did not allow testing of temporal precedence for the mediation models. All constructs were assessed via self-report. CONCLUSIONS: Attentional control appears to impact depression and anxiety symptoms through rumination. The pathway between poor attentional control and emotion dysregulation via rumination suggests that interventions targeting attentional control may decrease maladaptive ruminative processes, leading to improved emotion regulation and reduced clinical symptomatology. Future studies should examine the stability of this mediational relationship over time (and in the face of targeted interventions).